2020
DOI: 10.1017/s1047951120000566
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy in a patient with double outlet right ventricle

Abstract: Background:The double outlet right ventricle is uncommon and usually makes patients have haemodynamic and structural complications. Having a hyperdynamic state, such as pregnancy, with volume overload is very risky for a patient with complex CHD (CCHD). The diagnosis in early stages can prevent cardiac complications. The multi-disciplinary assessment of the disease lets patients make choices in treatment and reproductive life.Objective:Present a case of a successful pregnancy in a patient with a rare CCHD.Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The outcome of the baby was good after the delivery and follow up 4 years after the delivery persalinan. 14 Another case that was reported by Gu et al at 2016 also had the same DOR, patient also pregnant for second time after her first pregnancy ended in abortion. Patient was scheduled for Cesarean Delivery under epidural anesthesia.…”
Section: Resultsmentioning
confidence: 79%
“…The outcome of the baby was good after the delivery and follow up 4 years after the delivery persalinan. 14 Another case that was reported by Gu et al at 2016 also had the same DOR, patient also pregnant for second time after her first pregnancy ended in abortion. Patient was scheduled for Cesarean Delivery under epidural anesthesia.…”
Section: Resultsmentioning
confidence: 79%
“…She had an uncomplicated normal vaginal delivery. 3 She had the previous history of a first-trimester abortion.…”
Section: Discussionmentioning
confidence: 99%
“…2 Only a few reports describing uncorrected double outlet right ventricle in pregnancy are described in the literature. 3,4 We report three pregnancies in a woman who also developed a COVID-19 infection after delivery.…”
mentioning
confidence: 96%
“…Moreover, there is a published case of successful pregnancy and delivery in 19-years old patient with DORV. 27 It is a difficult task to compare children and adults with DORV due to high heterogeneity of this pathology in these cohorts. Yuan S. M. et al found that the adult patients with DORV more often reveal abnormal electrocardiogram (ECG) compared to pediatric patients, but the analysis showed no significant differences in LV function, prescribed medications, and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, some patients with partially naturally corrected DORV maintain the acceptable functional status until the third or even fifth decade of life. Moreover, there is a published case of successful pregnancy and delivery in 19‐years old patient with DORV 27 . It is a difficult task to compare children and adults with DORV due to high heterogeneity of this pathology in these cohorts.…”
Section: Introductionmentioning
confidence: 99%